Modeling the Effects of Safety Culture Affecting Safety Performance on Occupational Accidents with System Dynamics - Küçük, İbrahim; Yağımlı, Mustafa; Işıktaş, İsmail (International Journal of Computational and Experimental Science and Engineering, 2024)
Despite the advancement of technology in the world, human safety and occupational health are still exposed to numerous hazards in working life. Due to the heavy material and moral burden that occupational accidents will create on the socio-economic structure due to the lack of safety culture, countries are constantly looking for alternative safety culture policies to prevent occupational accidents. In our study, the role of safety practices, pressures and other conditions to reduce occupational accidents and the relationships between them were examined. The aim of the study is to present a System Synnamics (SD) model that can show the frequency values, costs, level of system safety and risks associated with accidents, human resources and productivity performances of occupational accidents in a certain time period. For this purpose, the behaviors of the factors affecting safety management in order to reduce occupational accidents have been analyzed, and the complexity of the causal factors affecting safety performance and safety culture has been revealed. In the next step, basic variables were defined, causal diagrams and flow diagrams were drawn, and a model was prepared with Stella Archtect 3.3 software and the data was simulated. Four different scenarios were defined in order to evaluate the sensitivity of the model and to determine the leverage variables. As a result of our study, the effects of both the safety management scenario and the human resources management scenario that cause a significant decrease in the number of accidents were seen. Another important aspect of the model we prepared in the study is the expansion and development of the model by adding new modules to create different Safety models. As a result of the study, compared to other scenarios, the safety management scenario has reduced the number of unsafe situations and unsafe behaviors, the number of incidents, the number of risks, the effect of occupational accidents and the effect of accident costs; It has been found that with the focus on safety, it causes an increase in its effect on production efficiency and on the basis of its contribution to more efficient use of human resources.